363 ADHERENCE TO AMERICAN ACADEMY OF PEDIATRICS PRACTICE GUIDELINES FOR URINARY TRACT INFECTIONS AT OUR TEACHING INSTITUTION. Issue 1 (1st January 2007) - Shah, L.; Mandlik, N.; Kumar, P.; Andaya, S.; Patamasucon, P.
Abstract : Introduction: Urinary tract infection (UTI) is becoming a more common cause of bacterial infection for febrile illness in children. The American Academy of Pediatrics (AAP) developed "practice guidelines" for the management of UTI in children in 1999. The aim of this study was to evaluate the uniformity of adherence to AAP guidelines at our teaching institution. Methods: The medical records of 405 patients (age 0-16 years) were retrospectively reviewed from the outpatient clinic, emergency room, and inpatient unit. Of these, 104 patients met the criteria. Data collected included age, gender, age of first UTI, presenting symptoms, method of urine collection, urinalysis, Gram stain, urine culture, repeat culture, imaging studies including renal ultrasonography (RUS), voiding cystourethrogram (VCUG), and treatment prescribed. UTI was defined as > 50, 000 cfu/mL for catheterized specimens and > 10 5 cfu/mL for clean catch specimens. Results: Overall, adherence to guidelines was as high as 97.1% in performance of urinalysis and 61% in imaging studies and 51% in urine Gram stains. The majority of patients who were tested for UTI presented with fever and 70% of urine specimens were collected by transurethral catheterization. The route of antibiotic administration for treatment of UTIs was exclusively parenteral in 12.5% of patients (mostly neonates < 1 month old), and 87.5% received a combination of parenteral and oral antibiotics at some point during the course of therapy. There was 70% adherence to the recommendations for the method of urine collection and 97% adherence to performance of urinalysis. In contrast, there was only 61% adherence for renal imaging. Reasons for the lower adherence rate for renal imaging included the following: 27% never came for follow-up and 7% did not get imaging due to lack of financial coverage. The attending physician did not order imaging studies in 24 patients, which occurred more frequently with community physicians than academic faculty. Escherichia coli was found to be the cause of UTI in 82.7% of patients, followed by Enterococcus spp, Staphylococcus spp, and then Proteus mirabilis/Klebsiella/Streptococcus . Conclusion: We conclude that there is great adherence to AAP guidelines for diagnosis of UTI, but there was less adherence to recommendations for renal imaging. Future studies to improve patient follow-up, financial coverage to improve access to care, and education of primary care providers to adherence of guidelines may increase the quality of care for children with UTI.